2011
DOI: 10.4061/2011/214940
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Atrial Fibrillation: A Review

Abstract: Atrial fibrillation is the most commonly sustained arrhythmia in man. While it affects millions of patients worldwide, its incidence will markedly increase with an aging population. Primary goals of AF therapy are to (1) reduce embolic complications, particularly stroke, (2) alleviate symptoms, and (3) prevent long-term heart remodelling. These have been proven to be a challenge as there are major limitations in our knowledge of the pathological and electrophysiological mechanisms underlying AF. Although advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although arrhythmia, e.g. sinus bradycardia, is a well-known postoperative complication of the Maze procedure [2], only a few reports have described thrombus formation in the left atrium (LA) after this procedure [3,4]. We experienced a case in which a rare appearance of a large mural thrombus was detected in the LA as late as two years after the Maze procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Although arrhythmia, e.g. sinus bradycardia, is a well-known postoperative complication of the Maze procedure [2], only a few reports have described thrombus formation in the left atrium (LA) after this procedure [3,4]. We experienced a case in which a rare appearance of a large mural thrombus was detected in the LA as late as two years after the Maze procedure.…”
Section: Introductionmentioning
confidence: 99%
“…endoscopic ablation. 10 Several single-center studies reported overall 1-year freedom from AF between 62% and 80%. 7,[11][12][13] The longest follow-up was reported by Hu and colleagues.…”
Section: Recurrence Of Atasmentioning
confidence: 99%
“…Patients who return to SR after mitral valve replacement or repair demonstrate better survival and freedom from adverse events. After the success of the Cox maze III procedure in treating AF, several surgeons began to add the maze procedure as an adjunct to mitral valve surgery to treat both problems 81 . Successful restoration of SR has been achieved in 70-96% of patients.…”
Section: Rheumatic Valvular Heart Disease and Atrial Fibrillationmentioning
confidence: 99%